The attitudes of graduate healthcare students toward older adults, personal aging, health care reform, and interprofessional collaboration. Issue 1 (January 2014) - Golden, Adam G.; Gammonley, Denise; Hunt, Debra; Olsen, Edwin; Issenberg, S. Barry
Abstract Healthcare reform has led to an increased emphasis on interprofessional healthcare models for older adults. Unfortunately, best practice education that focuses on the interprofessional healthcare of the elderly does not yet exist. As a prelude to implementing interprofessional geriatric educational initiatives, we developed a survey to identify potential attitudinal differences among graduate healthcare students regarding personal aging, caring for older adults, healthcare reform and the role of the physician on the interprofessional team. We surveyed third-year medical students, nurse practitioner students and graduate social work students. Attitudes regarding personal aging were similar among the professions. Nurse practitioner and social work students had higher positive attitudes toward the care of older adults. Concerns about the impact of healthcare reform on quality and healthcare costs differed significantly. There was also a significant difference in attitudes concerning the role of the physician as the leader of the interprofessional team. These results provide insights into gerontologic-focused attitudes of graduate healthcare professional students. In an era of dramatic healthcare change, these findings will assist educators in the development and implementation of educational programs to prepare graduate students for the interprofessional care of elderly patients.